Milk-derived bioactive peptides - Phareichon Kashung; Devi Karuthapandian (Food Production, Processing and Nutrition)
Abstract Bioactive peptides are the functional concept that refer to fragments of proteins that provide both functional and nutritional benefits as a functional component. Milk has been widely exploited as a source of diverse bioactive peptides. Bioactivity of peptides depends on amino acid composition and sequence specific to bioactivity. The production of bioactive peptides can be carried out through classical and bioinformatics approaches. In the classical approach, enzymatic hydrolysis, simulated digestion and hydrolysis by microbial enzymes are included. In the bioinformatics approach, databases, QSAR modeling, molecular docking and design of experiments (DoE) with response surface methodology are employed for identification and characterization of bioactive peptides from milk proteins. Milk-derived peptides have been identified to be antihypertensive, anti-diabetic, cytomodulatory, antioxidative, antimicrobial, and mineral binding peptides with wide applications as nutraceuticals in commercial products and food preservatives in food industry. Hence, this review has attempted to provide insight into the approaches and applications of milk- derived bioactive peptides with nutraceuticals properties in the development of functional foods. Graphical Abstract